The effect of home bleaching agents on the surface roughness of five different composite resins: A SEM evaluation - DENİZ, ŞULE TUĞBA; Cengiz, Esra; Kurtulmus-Yilmaz, Sevcan; Ulusoy, Nuran; Deniz, ŞULE TUĞBA; Yuksel-Devrim, Ece (My University, 2016)
The aim of this study was to investigate the effect of hydrogen peroxide (HP) and carbamide peroxide (CP) on the surface roughness of five different composite resins using profilometer and scanning electron microscope (SEM). Thirty-six specimens (1mm thick, 10mm in diameter) of five composite resins were fabricated. Each composite group was equally divided into three subgroups as control, CP and HP. In control group, specimens were stored in daily refreshed distilled water during the 14-day testing period. In other groups, 10% HP (Opalescence Treswhite) and 10% CP (Opalescence PF) were applied and surface roughness values (Ra) of each specimen were measured with a profilometer at the end of 14 days. Additionally, SEM analysis was performed to evaluate the surface deformations of composite resins. Data were analyzed with Kruskal-Wallis and Mann-Whitney U tests. Ra values of composite groups exposed to bleaching agents were statistically higher than control group (p<0.05). There was no significant difference between Ra values after HP and CP application within each composite group while SEM micrographs showed higher surface alterations at HP group compared to CP. Among the composite resins tested, Ceram-X Mono revealed the lowest Ra values after CP and HP applications as seen at SEM images. Home bleaching agents increased the surface roughness of all composites. Except CP applied Ceram-X mono specimens, Ra values of all composite resins evaluated in this study exceeded the critical limit of 0.2m. Ceram-X mono was the least affected composite material after bleaching application. SCANNING 38:277-283, 2016. (c) 2016 Wiley Periodicals, Inc.